2013
DOI: 10.1038/srep02295
|View full text |Cite
|
Sign up to set email alerts
|

Mass fabrication and delivery of 3D multilayer μTags into living cells

Abstract: Continuous monitoring of in vivo biological processes and their evolution at the cellular level would enable major advances in our understanding of biology and disease. As a stepping stone towards chronic cellular monitoring, we demonstrate massively parallel fabrication and delivery of 3D multilayer micro-Tags (μTags) into living cells. Both 10 μm × 10 μm × 1.5 μm and 18 μm × 7 μm × 1.5 μm devices containing inductive and capacitive structures were designed and fabricated as potential passive radio-frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…However, here we have shown that with proper surface functionalization these cells can readily internalize WGM resonators with volumes 300-fold larger than this, thus revealing a surprising ability of cells to internalize large polymer spheres. We also demonstrated an increase in the dimensions of phagocytosed objects for macrophages, with earlier reports showing uptake of spherical objects with diameters of up to 12.5 μm2226 and eliptical disks of up to 18 μm × 7 μm × 4 μm2234. Importantly, our study shows that microresonator internalization is highly feasible for all cell types investigated here, including cells generally understood to be non-phagocytic, like HEK 293, N7, and SH-SY5Y.…”
Section: Discussionsupporting
confidence: 84%
“…However, here we have shown that with proper surface functionalization these cells can readily internalize WGM resonators with volumes 300-fold larger than this, thus revealing a surprising ability of cells to internalize large polymer spheres. We also demonstrated an increase in the dimensions of phagocytosed objects for macrophages, with earlier reports showing uptake of spherical objects with diameters of up to 12.5 μm2226 and eliptical disks of up to 18 μm × 7 μm × 4 μm2234. Importantly, our study shows that microresonator internalization is highly feasible for all cell types investigated here, including cells generally understood to be non-phagocytic, like HEK 293, N7, and SH-SY5Y.…”
Section: Discussionsupporting
confidence: 84%
“…For our application, the device size and detection range have already been set. We limit the RFID diameter to be less than 25 µm, which is the typical size of mouse macrophages that have previously been demonstrated to internalize similar dummy RFID structures [19]. Since the RFIDs are flown through a thin microfluidic channel above the TRX detector, the detection range is a few micrometers.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…To test the biocompatibility of the RFID, the confluent culture of mouse melanocytic melanoma cells was incubated with RFID tags for 42 hours and imaged at intervals of three minutes to capture cell uptake of the RFID chips in a procedure described in [19]. The cell concentration was about 2 × 10 3 cells/mL, and the RFID-to-cell ratio was about 1 to 1 .…”
Section: Biocompatibility Verificationmentioning
confidence: 99%
See 2 more Smart Citations